Value Addition in Mobile Services and MMS - Goyal, Naresh; Goel, Vaishali; Kapoor, Sandeep (Journal of Commerce and Trade, 2009)
Mobile value-added services (MVAS) are those services that are not part of the basic voice service and are availed off separately by the end user. They are used as a tool for differentiation and allow the mobile operators to develop another stream of revenue. The nature of value added services change over time. Mobile operators provide the following value added service:- MMS, Voice SMS, Contest Service, Interactive Media, M-commerce, Missed Call Alert, Multimedia services, Mobile Marketing, M-search, Music, Phone back up, Ring Back Tone. This paper makes an attempt to understand the attitude of the people from different fields towards the MMS in terms of Prestige, Fun, Blackmailing, Quick sharing, and Promotional campaign.